2022
DOI: 10.3390/jcm11164724
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Prognostic Factors for Intense Pulsed Light Treatment with a Vascular Filter in Patients with Moderate or Severe Meibomian Gland Dysfunction

Abstract: We aimed to investigate the prognostic factors for, and treatment efficacy of, intense pulsed light (IPL) treatment with a vascular filter in patients with moderate or severe meibomian gland dysfunction (MGD). In this retrospective observational study, 58 moderate or severe MGD patients who underwent IPL treatment with a vascular filter were enrolled. IPL treatment was administered to the upper and lower eyelids four times at two-week intervals. At baseline, and four weeks after IPL, we evaluated the matrix me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Such exclusion of these wavelengths reduces the risk of overheating the epidermis and increases the amount of light absorbed by haemoglobin. 45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such exclusion of these wavelengths reduces the risk of overheating the epidermis and increases the amount of light absorbed by haemoglobin. 45 …”
Section: Discussionmentioning
confidence: 99%
“…The vascular filter decreases the amount Such exclusion of these wavelengths reduces the risk of overheating the epidermis and increases the amount of light absorbed by haemoglobin. 45 Theoretically, chemical reactions directly depend on temperature. The higher the temperature, the faster a given chemical reaction will proceed to destroy the P. acnes.…”
Section: Beforementioning
confidence: 99%
“…Few studies have investigated which patient population might benefit the most from IPL therapy. Patients who are younger tend to respond better to IPL [41,42]. Additionally, patients with moderate MGD, compared to severe MGD, seem to have a greater benefit with IPL therapy [43].…”
Section: Which Patients Respond Best To Treatment With Intense Pulsed...mentioning
confidence: 99%
“…The results showed that following surgery, patients who had IPL-MGX therapy saw a substantial improvement in meibomian gland function and a reduction in chalazion recurrence. IPL warms the skin internally to 50 °C helps liquefy aberrant meibum and assists telangiectasias to absorb more energy to closure abnormal vessels 14 , 15 . This has led to the interest in IPL as a potential therapy for chalazion.…”
Section: Introductionmentioning
confidence: 99%